ICD-9-CM international classification of diseases, ninth revision, clinical modification, sixth edition. - Centers for Disease Control (U.S.); United States. Health Care Financing Administration; National Center for Health Statistics (U.S.) ([Washington, D.C.] : U.S. Dept. of Health and Human Services, Centers for Disease Control and Prevention, Health Care Financing Administration, 1997)
Complete Oct. 1, 1997 version of the International Classification of Diseases, 9th revision, Clinical modification (volumes 1, 2, and 3, and guidelines), compiled by the National Center for Health Statistics and the Health Care Financing Administration. Includes tabular list of diseases and alphabetical index in three sections (Index to Diseases and Injuries; Table of Drugs and Chemicals; and Index to External Causes of Injuries and Poisonings). Organized into a hierarchy of major terms and various levels of subterms, and searchable by word, number, phrase, or field.
Title from disc label.
Issued October 1997.
System requirements: 386 IBM-compatible PC; 4MB RAM; Windows; VGA or SVGA monitor; 5MB hard disk space; CD-ROM drive.
Keywords: Nosology -- Databases; Diseases -- Databases